Lysosomal integral membrane protein-2 (LIMP-2/SCARB2) is involved in lysosomal cholesterol export - Saskia Heybrock (Nature Portfolio, 2019)
Cholesterol transport is tightly regulated in the cell and in lysosomes is regulated by NPC1/2. Here, Heybrock et al. use molecular modeling, knockout mice and cell based studies to show that LIMP-2 also mediates lysosomal cholesterol transport.